Research on the effect of mixture quality on the exhaust gas emissions of a petrol engine - College of Aeronautics, (Cranfield) (College of Aeronautics, 1968)
To meet the existing and proposed legislation for the control of air pollution by the exhaust emissions of petrol engines, a major research effort is required within the next five years. Not only are the regulations expected to become more stringent as the number of motor vehicles increases, but improvements will show a diminishing; return in terms of the percentage reduction of emissions when primary factors have been treated. A fundamental problem that is not well understood is the effect of the quality of the fuel-air mixture on combustion in the spark ignition engine. Knowledge of this factor could be important when the emissions are at a low level as a consequence of the employment of devices that treat factors such as mixture strength or the distribution of the fuel. Although the devices are effective in the reduction of the concentrations of hydrocarbons it is thought that many have an undesirable effect on the concentrations of the oxides of nitrogen. To improve the knowledge of these problems, it is the proposal that the research at the Advanced School of Automobile Engineering should be extended to a comprehensive study of the effects of mixture quality on the concentrations of carbon monoxide, hydrocarbons and oxides of nitrogen in the exhaust gas of a spark ignition engine. The facilities at the School are comprehensive and no financial assistance is requested for equipment. To allow the study to be completed within a time that is relevant to the urgency of the problem, a grant is requested for the employment of a Senior Technical Officer and a Laboratory Technician for a period of three years.